2012
DOI: 10.1080/87565641.2011.583301
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Status at Initial Presentation Predicts Neuropsychological Functioning in Early Onset Anorexia Nervosa at Four-Year Follow Up

Abstract: This study explores whether neurobiological status (indexed by regional cerebral blood flow) at initial presentation predicts neuropsychological status at four-year follow up in a sample of children with early onset anorexia nervosa. Neuropsychological assessment was conducted on 15 females four years after their initial treatment, and matched controls. At follow up there were significant differences between subgroups (based on neurobiological status at initial presentation) and matched controls in long-term v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Four studies did not use Booth's [14], method to score the ROCFT, but instead reported the accuracy score for the delayed recall. Frampton et al, [28] reported significant differences between the hypoperfusion AN groups and the HC group in delayed visual recall of the ROCFT with AN group performing worse (p=0.001, d=2.35, huge effect). There were no differences in performance between the normal perfusion AN group and the HC group.…”
Section: Synthesis Of Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Four studies did not use Booth's [14], method to score the ROCFT, but instead reported the accuracy score for the delayed recall. Frampton et al, [28] reported significant differences between the hypoperfusion AN groups and the HC group in delayed visual recall of the ROCFT with AN group performing worse (p=0.001, d=2.35, huge effect). There were no differences in performance between the normal perfusion AN group and the HC group.…”
Section: Synthesis Of Resultsmentioning
confidence: 97%
“…The ROCFT was used in 6 studies [21,22,24,[26][27][28]. The methods for scoring the ROCFT varied between studies with the most consistently used method of scoring was Booth's (2006) where by the order and style indices are calculated and contribute to a central coherence index (CCI).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the huge number of variables, it is difficult to demonstrate the correlation between brain and functional changes [56]. In the case of AN, there is a preliminary study in which patients at an early stage were evaluated, and it was found that the neurobiological abnormalities may predict neuropsychological difficulties during follow-up [57]. This could be an indication that some neuropsychological disorders appear previously, so the weight of the disposition and the consequences of each type of ED should be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia (Bagby et al, 1994;Taylor & Bagby, 1988) Difficulty in detecting emotional signals from self (Harrison, Sullivan, Tchanturia, & Treasure, 2010;Rastam et al, 1997;Troop et al, 1995) Difficulty in detecting emotional signals from others (Harrison et al, 2010;Kucharska-Pietura et al, 2004;Zonnevijlle-Bender, van Goozen, CohenKettenis, van Elburg, & van Engeland, 2002) Poor IA (Garner, 2004;Garner, Olmsted, & Polivy, 1983) Feeling confused and/or fearful and non-accepting about one's own and others' emotional responses (Corstorphine, Mountford, Tomlinson, Waller, & Meyer, 2007;Fox, 2009;Ioannou & Fox, 2009) Difficulty in identifying visceral sensations related to hunger and satiety (Garner, 2004;Merwin, Zucker, Lacey, & Elliott, 2010) Anxiety, harm avoidance, and inhibition (Kaye, 2009;Schmidt & Treasure, 2006) Serotonergic disturbance Lilenfeld, Wonderlich, Riso, Crosby, & Mitchell, 2006) Dysfunction or 'disconnection' of neural networks converging upon the insula cortex Delayed visual recall and cognitive inhibition; misinterpreting others' facial expressions and responses; higher degree of negative attitude toward emotions and lower emotional expressiveness; slower time on facial recognition in comparison to healthy controls (Frampton, Hutchinson, Watkins, & Lask, 2012;Jansch et al, 2009;Kucharska-Pietura et al, 2004;Nunn et al, 2008;Pollatos et al, 2008) Numbing effects of starvation (Keys et al, 1950) Dietary restraint helps avoid uncomfortable bodily sensations (e.g. fullness) and affective experiences, for example, guilt and shame Schmidt & Treasure, 2006) 24 M. Tantillo et al…”
Section: Phenomena Involving Proposed Intrapersonal Processesmentioning
confidence: 98%